2010
DOI: 10.4103/0377-4929.59180
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and cigarette smoking: Impact of two major lifestyle factors on male fertility

Abstract: Asthenozoospermia, the most common semen variable in our study, can be an early indicator of reduction in quality of semen. Alcohol abuse apparently targets sperm morphology and sperm production. Smoke-induced toxins primarily hamper sperm motility and seminal fluid quality. Progressive deterioration in semen quality is related to increasing quantity of alcohol intake and cigarettes smoked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
3
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(104 citation statements)
references
References 2 publications
6
89
3
6
Order By: Relevance
“…Studies on both human and animal laboratories have scientifically demonstrated that alcohol consumption impaired hypothalamic-pituitarygonadal (HPG) axis (Little et al, 1992;Maneesh et al, 2006), reduced testosterone level in the testes (Muthusami & Chinnaswamy, 2005) and diminished sperm quality. The sperm quality that are tremendously affected include, sperm concentration (Martini et al, 2004;Condorelli et al, 2014), morphological abnormalities (Joo et al, 2012) and sperm motility (Gaur et al, 2010). These finding were reported contrarily across other studies where they find no association between alcohol consumption and sperm quality (Kunzle et al, 2003;Teijon et al, 2007;Li et al, 2009;Hansen et al, 2012;Povey et al, 2012;Jensen et al, 2014).…”
Section: Introductioncontrasting
confidence: 45%
“…Studies on both human and animal laboratories have scientifically demonstrated that alcohol consumption impaired hypothalamic-pituitarygonadal (HPG) axis (Little et al, 1992;Maneesh et al, 2006), reduced testosterone level in the testes (Muthusami & Chinnaswamy, 2005) and diminished sperm quality. The sperm quality that are tremendously affected include, sperm concentration (Martini et al, 2004;Condorelli et al, 2014), morphological abnormalities (Joo et al, 2012) and sperm motility (Gaur et al, 2010). These finding were reported contrarily across other studies where they find no association between alcohol consumption and sperm quality (Kunzle et al, 2003;Teijon et al, 2007;Li et al, 2009;Hansen et al, 2012;Povey et al, 2012;Jensen et al, 2014).…”
Section: Introductioncontrasting
confidence: 45%
“…Alcohol causes impaired testosterone production and thereby has great impact on fertility and potency. It also has deleterious effect on sertoli cells, thereby decreasing LH, FSH production [19], [20]. Spermatogenesis is sensitive to a variety of chemical and physical stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study by Gaur et al on 100 alcoholic showed oligozoospermia was much higher amongst alcohol cases (n=51), than controls, indicating progressive damage to testes in direct relation to increasing daily alcohol intake. 11 These studies showed lesser association of asthenozoospermia as compared to oligozoospermia. Thus, alcohol induced reduction in levels of testosterone, LH and FSH not only hamper their normal morphological development and maturation of spermatozoa, it slows down the sperm production by testicular germ cells, especially in alcoholic.…”
Section: Aswal a Et Al Int J Reprod Contracept Obstet Gynecol 2017 mentioning
confidence: 99%
“…Our results corroborated well with other studies like ones by Gaur et al, Khushbu et al and Kumar et al (Table 6). 10,11,14 Hence it is evident that alcohol consumption, tobacco smoking and tobacco chewing have a significant negative effect on the process of spermatogenesis, ultimately affecting sperm concentration, viability and motility. Hence clinician and fertility counselors need to be more focused to control infertility by modifying the life style factors.…”
mentioning
confidence: 99%